The Challenge of 'Territory': Weaving the Social Fabric of Indigenous Communities in Nicaragua's Northern Caribbean Autonomous Region - Larson, A.M.; Soto, F.; Mairena, D.; Moreno, E.; Mairena, E.; Mendoza Lewis, J. (Wiley, 2016)
In Nicaragua, indigenous and afro‐descendant peoples' demands for territorial rights have become inseparable from demands for the exercise of autonomy in the Caribbean Coast. Alone, the new titles obtained by these communities, like the autonomy regime, will not guarantee legal security over collective lands, control over natural resources or the exercise of free determination. Through the analysis of three indigenous territories in Nicaragua's Northern Caribbean Coast Autonomous Region (RACCN), the article argues that the state is still setting the terms of debate. It suggests that the defence of rights should be anchored not only on the ownership of territory but also on the social fabric of indigenous communities and territories.